ANALISIS VISUAL KARYA FINGER PAINTING DI TK KUSA WAHANA GIRI - I Gde Suryawan, Surya; Sindu Putra, Ida Bagus Komang (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2022)
Finger painting is one of the learning methods applied to formal education units at Kusa Wahana Giri Kindergarten, this learning is applied because it has a very important function for the development of fine motor skills in early childhood. Many benefits are obtained in learning finger painting including finger painting as a media tool to express their art, finger painting trains children to concentrate so that as therapy for hyperactive children, finger painting has the potential for psychological health. This study uses a qualitative approach with descriptive analysis. Methods and techniques of data collection using observation techniques. The results of this study indicate that the results of the Visual Analysis of Finger Painting Work at Kusa Wahana Giri Kindergarten have advantages such as the lines, areas, colors, and textures produced are very varied. This can be seen in children’s works such as the existence of various lines, both soft lines, curved lines, harmonious lines, and so on. Children are also able to present real textures and pseudo textures. This texture is the result of the combination of the color traces that are scratched by the children in the field. The color combination is good from warm colors, cool colors, and neutral colors. This shows that through finger painting children can explore the ability to process taste and also help children hone their motor system to become more responsive